Contribution to the study of Myroxylon peruiferum Lin. Fil. - Maldonado, Angel (1920)
The purpose of this paper is to provide some notes for study farmacográfico Myroxylon peruiferum Lin. fil; but we thought it useful to give an introduction, some facts about the history and origin of the different botanical balms are exported to America; at the same time allow us to propose a specific name for the pathological resinous flow Myroxylon peruiferurn Lin. fil. and label it well so of being able to easily distinguish from other naval stores, from the botanical family Leguminosae, and to complete this introduction, we will also deal laconically, the origin of the other resinous substances farmacográfica family of Benzoic (HERAIL) from America.